1996
DOI: 10.1007/bf00377230
|View full text |Cite
|
Sign up to set email alerts
|

Muscle regeneration in the holothurian Stichopus japonicus

Abstract: The regeneration of longitudinal muscle bands (LMBs) in the sea cucumber Stichopus japonicus was studied using light and electron microscopic and immunocytochemical methods. Previous investigations of holothurian organs showed the presence of some cytoskeletal proteins which were specific for LMBs only. One of them, the 98 KDa protein, was isolated by means of SDS-electrophoresis and used as an antigen to obtain polyclonal antibodies. When tested on paraffin sections of sea cucumber organs, the antibodies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 12 publications
1
34
0
Order By: Relevance
“…The number of muscle cells labeled with BrdU per area in the regenerated animals was found to peak during the second week of regeneration. Each point represents the mean percentage + SE of at least three animals Candia-Carnevali et al 1993, 1995Dolmatov et al 1996;VandenSpiegel et al 2000). Moreover, studies from other regenerating echinoderm species further support the coelomic epithelium as the origin of the new muscle cells.…”
Section: Muscle Cell Originsmentioning
confidence: 85%
See 1 more Smart Citation
“…The number of muscle cells labeled with BrdU per area in the regenerated animals was found to peak during the second week of regeneration. Each point represents the mean percentage + SE of at least three animals Candia-Carnevali et al 1993, 1995Dolmatov et al 1996;VandenSpiegel et al 2000). Moreover, studies from other regenerating echinoderm species further support the coelomic epithelium as the origin of the new muscle cells.…”
Section: Muscle Cell Originsmentioning
confidence: 85%
“…Moreover, studies from other regenerating echinoderm species further support the coelomic epithelium as the origin of the new muscle cells. The role of the coelomic epithelium in longitudinal muscle regeneration has been elegantly shown by Dolmatov and colleagues in several holothurian species (Dolmatov et al 1996;Dolmatov and Ginanova 2001). Using a coelomic epithelium-specific antibody or labeled thymidine together with microscopic analysis, they have shown that, when the longitudinal muscle is damaged, cells of the overlying coelomic epithelia differentiate into myocytes.…”
Section: Muscle Cell Originsmentioning
confidence: 95%
“…During this period, the closure of the wound and the histolysis of the damaged tissues occurs. After evisceration in A. japonicus, a clot of coelomocytes form at the wound site, as occurs in most echinoderms (Kille 1935;Menton and Eisen 1973;Candia Carnevali et al 1989;Dolmatov 1992;Dolmatov et al 1996;Mozzi et al 2006), except at sites of minor damage, e.g. after the discharge of Cuvierian tubules (VandenSpiegel et al 2000).…”
Section: Stages Of Regenerationmentioning
confidence: 95%
“…In order to obtain the full picture, one must also study a variety of processes that take place during muscle morphogenesis. A number of reports on the development, growth and regeneration of myoepithelial cells and muscles in echinoderms, particularly holothurians (Dolmatov and Ivantey 1993;Dolmatov 1992Dolmatov , 1995bDolmatov et al 1994Dolmatov et al , 1996VandenSpiegel et al 2000;Dolmatov and Ginanova 2001;Mashanov and Dolmatov 2001;Candelaria et al 2006), has been published. On the other hand, the development of the echinoid lantern muscles has not been studied at all.…”
Section: Introductionmentioning
confidence: 98%